A new species of the genus Antennoseius (Ascidae : Mesostigmata) from India - Bhattacharyya, A. K.; Sanyal, A. K.; Bhattacharya, T. (Zootaxa, 2003)
Antennoseius orientalis sp. nov. is described along with illustrations and a key to the Indian species of the genus is provided.